2021
DOI: 10.1007/s10872-021-00606-5
|View full text |Cite
|
Sign up to set email alerts
|

A review: iron and nutrient supply in the subarctic Pacific and its impact on phytoplankton production

Abstract: One of the most important breakthroughs in oceanography in the last 30 years was the discovery that iron (Fe) controls biological production as a micronutrient, and our understanding of Fe and nutrient biogeochemical dynamics in the ocean has significantly advanced. In this review, we looked back both previous and updated knowledge of the natural Fe supply processes and nutrient dynamics in the subarctic Pacific and its impact on biological production. Although atmospheric dust has been considered to be the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 213 publications
(341 reference statements)
0
14
0
Order By: Relevance
“…Recently Zhang et al (2021a), using observations from a biogeochemical-Argo float (BGC-Argo), showed that the seasonal variability in surface (~7 m) chlorophyll-a for this region was consistent with satellite observations: phytoplankton biomass begins to increase in late summer, reaching a distinct peak at the end of September before decreasing in late October and November. These bioregions occurred thus in waters characterized by iron-poor and nitrate- rich conditions (Martin et al, 1991;Boyd et al, 2004;Nishioka et al, 2021). Iron supply governs bloom dynamics in high-nitrate, low-chlorophyll (HNLC) areas, and Fe limitation prevents the occurrence of diatom blooms (i.e., large phytoplankton cells), which are frequent on the shelf (Ribalet et al, 2010), thus explaining the lack of marked spring phytoplankton blooms.…”
Section: Off-shelf and Shelf-break Bioregionsmentioning
confidence: 99%
“…Recently Zhang et al (2021a), using observations from a biogeochemical-Argo float (BGC-Argo), showed that the seasonal variability in surface (~7 m) chlorophyll-a for this region was consistent with satellite observations: phytoplankton biomass begins to increase in late summer, reaching a distinct peak at the end of September before decreasing in late October and November. These bioregions occurred thus in waters characterized by iron-poor and nitrate- rich conditions (Martin et al, 1991;Boyd et al, 2004;Nishioka et al, 2021). Iron supply governs bloom dynamics in high-nitrate, low-chlorophyll (HNLC) areas, and Fe limitation prevents the occurrence of diatom blooms (i.e., large phytoplankton cells), which are frequent on the shelf (Ribalet et al, 2010), thus explaining the lack of marked spring phytoplankton blooms.…”
Section: Off-shelf and Shelf-break Bioregionsmentioning
confidence: 99%
“…For instance, continental shelves can also be associated with complex topographic geometry and coarse resolution models may face similar challenges in properly representing the dispersal of tracers supplied, such as DFe. For instance, in the North Pacific, the DFe inputs from sediment resuspension disperses from the sea of Okhotsk into the wider North Pacific basin via North Pacific Intermediate Water (NPIW) (Nishioka et al, 2020(Nishioka et al, , 2021. An important component of this dispersal is the strong topographically induced diapycnal mixing that occurs over the Kuril straits (Yagi & Yasuda, 2012), transporting DFe onto the NPIW isopycnals to then spread throughout the North Pacific basin (Nishioka et al, 2020).…”
Section: Using Model-observation Studies To Quantify Iron Cycle Mecha...mentioning
confidence: 99%
“…Previous shipboard Fe-enrichment experiments in the western and eastern subarctic Pacific have shown that the addition of dissolved iron, which has a size < 0.2 or 0.45 µm (Gledhill and Buck, 2012), to in situ water significantly increased nutrient utilization and led to an enhancement in the concentration of chlorophyll (Martin and Fitzwater, 1988;Boyd et al, 1996;Tsuda et al, 2003;Marchetti et al, 2006a). This indicates that bioavailable Fe (BFe), which can be directly accessed by phytoplankton (Nishioka et al, 2021), limits phytoplankton growth, especially diatom growth, in these two regions, and that BFe limitation was also the cause of the HNLC conditions in the subarctic Pacific (Martin et al, 1991;Harrison et al, 2004;Marchetti et al, 2006b). In the eastern subarctic Pacific, the dissolved Fe concentration and the bioavailability of Fe are both lower than those in the western subarctic Pacific (Harrison et al, 2004;Nishioka et al, 2007;Kondo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Papa, the seasonal variability of chlorophyll is weak (0.2-0.6 mg m −3 ), but concentrations are slightly higher in late summer (Mochizuki et al, 2002;Pena and Varela, 2007;Matsumoto et al, 2014). The mechanisms underlying these marine ecosystems on the two sides of the subarctic Pacific have been actively investigated, and they have been found to be related to the differences in Fe bioavailability in explored in several studies (Banse and English, 1999;Harrison et al, 1999;Fujii et al, 2007;Nishioka et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation